A Comparative Analysis of the Trade and Industrial Policies of Ukraine and China in the Context of the Obor Initiative - Tamara Ostashko; Volodymyr Olefir; Vitalii Venger; Olena Boiko (Comparative Economic Research. Central and Eastern Europe, 2021)
The world economy is evolving towards multipolar globalization, and China has become a new pole of economic development. Ukraine, like other countries, is looking for ways to cooperate with China in the field of trade and investment. China, for its part, offers a model of cooperation within the framework of the OBOR (One Belt, One Road) initiative. Along with Chinese investment in transport and logistics infrastructure, OBOR aims to conclude FTAs with the countries participating in the initiative; thus, the article focuses on the issues of trade, and Ukraine's industrial and innovation policy in the context of the OBOR initiative. A comparative analysis of both countries' trade and industrial policies was conducted to provide a basis for evaluation. The terms of trade between Ukraine and China are not symmetrical due to the difference in the scale of the economy and trade. Additionally, Ukraine's trade regime is relatively liberal, while the Chinese market is protected by higher tariff and non-tariff barriers. Furthermore, the current situation in mutual trade is asymmetric. Ukraine exports mainly raw materials to China, while exports from China to Ukraine are dominated by investment and consumer goods. The import dependence of the Ukrainian economy, in general, is high without any noticeable signs of decline. In 2014-2018, the share of imports of goods and services in GDP in Ukraine averaged 54% (for comparison, in China, this parameter was 19%). In 2018, 55% of Ukraine's negative balance in trade in goods was due to trade with China. China seeks to conclude FTAs under the OBOR initiative, but in the current context, the liberalization of trade regimes with China will result in Ukraine growing its raw material exports to China and increasing its dependence on Chinese imports. On the other hand, China's investment, production, research, and technological opportunities can become an important resource for Ukraine to modernize its economy. Promising areas of Chinese investment include high technology, in particular, aviation, shipbuilding, bioengineering, the development of new materials, and more. Ukraine is interested in China's experience in implementing a number of state programs in the field of innovation development of Chinese industrial enterprises. The support system for clusters, industrial parks, Free Economic Zones (FEZs), and technology parks can be recommended for introduction into Ukrainian legislation in the sphere of developing an innovation structure in Ukraine.
Keywords: F13; F21; O38; O57; 330; One Belt One Road initiative; China; Ukraine; trade policy; FTA; industrial policy